Bioconversion of isoeugenol to vanillin with different straints of pseudomonas aeruginosa - Shuhada, Abdul Muttalib (2014)
The experiment was conducted at the Faculty of Industrial Sciences and Technology lab at Universiti Malaysia Pahang to investigate the bioconversion of isoeugenol to vanillin. Vanillin is a simple monoterpenoid which is considered as one of the world’s principal flavouring compound used extensively in the food, beverage, perfumery, and pharmaceutical industries. Vanillin can be produced using bioconversion of isoeugenol via microorganism and it could be used to substitute synthetic vanillin with a natural vanillin flavor at an affordable price. This study was conducted to screen the Pseudomonas ruginosa strains for the bioconversion of isoeugenol to vanillin. Initially isoeugenol was obtained from extraction of crude clove bud oil. Two different methods of extraction were done to extract the crude clove bud oil which were microwave extraction and steam distillation. Through microwave extraction of clove bud oil, eugenol can be extracted at minimum time of 75 minutes with an optimum yield of 9.09% as compared to the steam distillation technique where it took time to achieve higher yield of eugenol. Purified ugenol (purity ≥99%) was obtained using 1.2 moles of sodium hydroxide with recycle water. Ruthenium acetylacetonate was used as catalyst to produce isoeugenol by synthesis. The conversion was almost 99% but the method is very expensive and cannot be further use s a substrate in biotransformation process. API-20E test was selected as a biochemical test to identify the characteristics of Pseudomonas aeruginosa strains P178, U641, S376, B932 nd ETT187. In fact, all Pseudomonas aeruginosa strains were also confirmed using 16S rRNA gene sequencing and obtained that all the strains were Pseudomonas aeruginosa. In this study, the subculture of different strains of Pseudomonas aeruginosa was used to onvert isoeugenol to vanillin by oxidation. Vanillin formation was analyzed directly by s chromatography mass spectrometry (GCMS). All the strains exhibited good potential as whole-cell bio-catalysts for direct bioconversion of isoeugenol to vanillin. During biotransformation screening by whole cell culture of P. aeruginosa strains, P. aeruginosa ETT187 showing a good vanillin produced which is 2.312±0.006 g/l at only 1% (v/v) isoeugenol added for 24 hours incubation at 200 rpm agitation. Furthermore, the effect of nillin production versus time with 1% induction of isoeugenol was observed at 12, 24, 36, 48, 60, 72, 84, and 96 hours. P. aeruginosa P178 demonstrated consist the highest oduction of vanillin which was 2.97g/l at 72 hours of incubation while the isoeugenol creased over time. Meanwhile, P. aeruginosa ETT 187 presented the highest amount of nillin produced in only 24 hours with 2.31 g/l. Furthermore, strains U641, S376 and 932 produced the highest amount of vanillin at maximum of 96 hours with 2.62 g/l, 3.56 g/l and 2.49 g/l respectively. The reaction also produced the following by-products, namely, isovanillic acid and isovanillin, ethyl vanillate and also vanillyl methyl ketone. As a onclusion, the P. aeruginosa strains which were P. aeruginosa P178, P. aeruginosa U641, P. aeruginosa S376, P. aeruginosa B932 and P. aeruginosa ETT187 can be proposed to pilot scale as bicatalytic to convert isoeugenol to vanillin at a reasonable price.